1999
DOI: 10.1159/000054505
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Response to the Adrenocorticotropin Test and the Combined Dexamethasone and Corticotropin-Releasing Hormone Test in Patients with Multiple Sclerosis

Abstract: Basic and clinical research suggest that disturbed neuroendocrine function may be involved in the pathogenesis and course of autoimmune diseases including multiple sclerosis (MS). Dehydroepiandrosterone (DHEA) in this connection is of particular interest as it appears to have effects on the immune system. Moreover, DHEA levels are decreased in chronic inflammatory diseases. To further investigate the role of DHEA in MS, we administered the adrenocorticotropin (ACTH) stimulation test and the combined dexamethas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…An increased cortisol/DHEAS ratio has been found to be a surrogate for neurodegenerative diseases[31][33]. Therefore, an alternative hypothesis is that the cortisol/DHEAS ratio may represent a slightly lower cerebral DHEAS production in relation to cortisol already before the stroke in predisposing patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased cortisol/DHEAS ratio has been found to be a surrogate for neurodegenerative diseases[31][33]. Therefore, an alternative hypothesis is that the cortisol/DHEAS ratio may represent a slightly lower cerebral DHEAS production in relation to cortisol already before the stroke in predisposing patients.…”
Section: Discussionmentioning
confidence: 99%
“…In longitudinal studies, an increased cortisol/DHEAS ratio has been found to accelerate atherosclerosis-related diseases [27] and to be predictive for cardiovascular diseases [28] and all-cause-mortality [29]. In chronic stress [30] and neurodegenerative diseases [31][33], higher cortisol and lower serum DHEA and DHEAS values with a consecutive higher cortisol/DHEAS-ratio have been found. In the acute setting, high cortisol and an increased cortisol/DHEAS – ratio upon admission is associated with severity of illness in intensive care patients [34], corresponding to an impaired adrenal androgen action [35].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining four subjects did not respond (Grasser et al 1996). Subsequent studies have confirmed that MS patients are able to escape from dexamethasone suppression following challenge with CRF, suggesting a hyperactivity of the HPA axis that is significantly correlated to disease activity (Fassbender et al 1998;Kumpfel et al 1999;Then Bergh et al 1999). However, although one study related this escape to higher depression and anxiety scores in MS patients compared to controls (Fassbender et al 1998), others have not found any evidence to relate the cortisol response to CRF with increased incidence of depression (Kumpfel et al 1999;Then Bergh et al 1999).…”
Section: Is the Hpa Axis Altered In Patients With Autoimmune Disease?mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Interestingly, hypoandrogenicity is a very common phenomenon in many chronic inflammatory diseases. [10][11][12][13][14][15][16][17] In RA and other autoimmune diseases it has been stated that alteration of androgen secretion has an impact on perpetuation of the disease. 18 19 Treatment with dehydroepiandrosterone (DHEA), as the starting-point of androgen conversion (fig 1), has been proved to be a therapeutic alternative in SLE [20][21][22] and, possibly, in patients with chronic inflammatory bowel disease.…”
mentioning
confidence: 99%